Effects of Small-Sided Games vs. Running-Based High-Intensity Interval Training on Physical Performance in Soccer Players: A Meta-Analytical Comparison - Clemente, Filipe Manuel; Ramirez-Campillo, Rodrigo; Afonso, José; Sarmento, Hugo (Frontiers in Physiology, 2021)
Objectives: This systematic review with meta-analysis (SRMA) was conducted to compare the effects of SSG-based interventions vs. running-based HIIT interventions on soccer players’ sprinting time (ST), vertical height jump (VJH), and change-of-direction time (CODt). Data sources: The data sources utilized were Web of Science, Scopus, SPORTDiscus, and PubMed. Results: An electronic search yielded 650 articles, six of which were included in the present study. Between-group analysis found a significant favoring effect of HIIT-based over SSG-based training interventions for the improvement of linear sprinting time (ES = 0.42; p = 0.012). A within-group analysis revealed a significant favoring effect of HIIT-based training interventions for improving linear sprinting time (ES = 0.42; p = 0.008) and CODt (ES = 1.04; p = 0.005) despite a non-significant effect on VJH (ES = 0.47; p = 0.22). Conclusions: The meta-analytical comparison revealed favoring the effect of running-based HIIT over SSG-based interventions in sprinting performance, although no significant differences were observed for jumping and change-of-direction performance. The findings suggest that SSG-based programs should be supplemented by other training methods that benefit determinant capacities in soccer players.